Preparation method of aluminum-based composite material for forming grain boundary and intragranular synergistic strengthening

By doping nano Al2O3 particles in the Al-TiO2 system, amorphous Al2O3 core-shell structure reinforced phase particles are formed with amorphous Al2O3 coated with TiO2, and plastic processing makes them enter the grains, solving the problem of strength decay in a high-temperature environment, and achieving excellent strong plasticity and high-temperature resistance.

CN119592829AActive Publication Date: 2025-03-11INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411779606.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The problems of strength decay and complex preparation processes of existing aluminum-based composite materials under high temperature environments.

Method used

By doping nano Al2O3 particles in the Al-TiO2 in situ reaction system, the sufficient reaction of Al-TiO2 is inhibited, forming a core-shell structure reinforced phase particles coated with TiO2 with amorphous Al2O3, and then entering the grains through plastic processing, achieving coordinated strengthening of grain boundaries-in-crystalline crystals.

Benefits of technology

The strong plasticity and high temperature resistance of aluminum-based composite materials are significantly improved, and the tensile strength can reach 216MPa at 350℃, and the strength does not decrease after 1000 hours of high-temperature annealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592829A_ABST
    Figure CN119592829A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an aluminum-based composite material capable of forming grain boundary and intragranular synergistic strengthening, relates to the technical field of powder metallurgy, and solves the problems that an existing aluminum-based composite material is poor in strong plasticity and insufficient in high temperature resistance. According to the main technical scheme, the preparation method of the aluminum-based composite material comprises the following steps that raw material powder is subjected to ball milling and mixing treatment; the raw material powder comprises aluminum powder, nano TiO2 powder and nano Al2O3 powder; carrying out sintering treatment on the powder subjected to ball milling and mixing treatment; in the sintering treatment process, Al and TiO2 are subjected to incomplete reaction, amorphous Al2O3 layers are generated on the surfaces of TiO2 particles, and core-shell structure strengthening phase particles with TiO2 coated with amorphous Al2O3 are formed; and carrying out plastic processing treatment on the sintered composite material to promote the core-shell structure strengthening phase particles of the amorphous Al2O3 coated TiO2 to enter the crystal grains to obtain the aluminum-based composite material. The method is mainly used for improving the strength, plasticity and high temperature resistance of the aluminum-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, and in particular to a method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening. Background Art

[0002] A significant limitation of the current aluminum alloy material system is its insufficient heat resistance. Traditional high-strength aluminum alloys can usually only maintain their superior performance in an environment below 100°C. Once the temperature rises to above 200°C, their strength will decline rapidly. Even Al-Si or Al-Cu series alloys designed for improving heat resistance have difficulty breaking through the threshold of 100MPa when reaching a high temperature of 350°C. On the other hand, aluminum alloys such as Al-Fe-V-Si that use dispersion strengthening technology can improve heat resistance, but their preparation process is extremely complex, and large-scale industrial production faces many challenges, which limits their wide application in practical engineering. For key components that operate for a long time under extreme temperature conditions (200-400°C), such as aircraft structural parts, engine components, and high-efficiency radiators, they currently rely on high-temperature resistant materials such as titanium alloys and stainless steel for preparation. However, although these materials meet the strength requirements in high-temperature environments, they are often accompanied by high weight, which brings difficulties to the lightweight design of equipment, thereby affecting the further improvement and breakthrough of overall performance indicators. Therefore, the development of new, lightweight aluminum alloy materials with excellent heat resistance has become an important research direction to improve the performance of equipment in related fields.

[0003] Using nano ceramic particles as strengthening phase can have very excellent thermal stability, thus obtain good high temperature resistance. However, the introduced strengthening phase is mostly located at the grain boundary, although it can play the role of pinning the grain boundary, the pinning effect on the intracrystalline dislocation is extremely weak, prompting the grain boundary to produce a large amount of dislocations in the loading process and concentrate and cause intercrystalline fracture, and the material toughness is insufficient. As through Al-TiO2 in-situ reaction, nano Al2O3 particles and Al3Ti particles can be introduced into the aluminum matrix. Among them, nano Al2O3 particles can pin the aluminum grain boundary to make the material have higher high temperature strength. However, nano Al2O3 particles are not easy to enter the grain interior, resulting in the inability to pin intracrystalline dislocations, and the high temperature strength is difficult to further improve, and it is easy to cause dislocations to concentrate near the grain boundary and cause intercrystalline cracking. In addition, Al3Ti particles are difficult to keep nano size, and the lifting effect on high temperature strength after coarsening is very low.

[0004] In summary, the current aluminum-based composite materials have the problems of poor plasticity and insufficient high temperature resistance. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing an aluminum-based composite material that forms grain boundary and intragranular synergistic strengthening, the main purpose of which is to improve the strength, plasticity and high temperature resistance of the aluminum-based composite material.

[0006] In order to achieve the above object, the present invention mainly provides the following technical solutions:

[0007] On the one hand, an embodiment of the present invention provides a method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening, wherein the method for preparing the aluminum-based composite material comprises the following steps:

[0008] Ball milling and mixing treatment: ball milling and mixing treatment is performed on the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes aluminum powder, nano-TiO2 powder, and nano-Al2O3 powder;

[0009] Powder metallurgy sintering treatment: sintering the powder after the ball milling mixing treatment to obtain a sintered composite material; wherein, during the sintering process, Al and TiO2 react incompletely, and an amorphous Al2O3 layer is generated on the surface of the TiO2 particles, forming a core-shell structure reinforcement phase particle in which the amorphous Al2O3 covers the TiO2;

[0010] Plastic processing: Plastic processing is performed on the composite material after the sintering process to promote the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 to enter the interior of the grains to obtain an aluminum-based composite material.

[0011] Preferably, in the raw material powder: the average particle size of the aluminum powder is 5 to 50 μm; and / or the average particle size of the nano TiO2 powder is 15 to 40 nm; and / or the average particle size of the nano Al2O3 powder is 15 to 50 nm.

[0012] Preferably, in the raw material powder: the volume fraction of the nano-TiO2 powder is 3-8%, and the volume fraction of the nano-Al2O3 powder is 1-3%.

[0013] Preferably, in the ball milling mixing step: the ball-to-material weight ratio is 15:1 to 30:1; and / or during the ball milling mixing process, the maximum linear velocity of the grinding balls is greater than 3.5 m / s; and / or the ball milling mixing process lasts for 4 to 20 hours.

[0014] Preferably, in the step of the powder metallurgy sintering treatment: before the sintering treatment, the powder after the ball milling mixing treatment needs to be cold pressed to improve the density.

[0015] Preferably, in the step of the powder metallurgy sintering treatment: the sintering treatment temperature is 580-645° C.; preferably, the sintering treatment time is 1-5 hours.

[0016] Preferably, in the step of the powder metallurgy sintering treatment: the sintering treatment adopts any one of vacuum hot pressing sintering treatment, hot isostatic pressing sintering treatment and discharge ion beam sintering treatment processes.

[0017] Preferably, in the step of plastic processing: the temperature of the plastic processing is 520-630°C; and / or the method of the plastic processing is any one of forging, rolling, and extrusion; and / or the deformation amount of the plastic processing is (6-30):1.

[0018] On the other hand, an embodiment of the present invention provides an aluminum-based composite material, wherein the microstructure of the aluminum-based composite material includes an Al matrix, amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles, and nano Al2O3 particles; wherein at least part of the amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles are located inside the grains; at least part of the Al2O3 particles are distributed at the grain boundaries;

[0019] Preferably, the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 with a volume fraction of more than 50% are located inside the grains;

[0020] Preferably, Al2O3 particles with a volume fraction of more than 80% are distributed at the grain boundaries;

[0021] Preferably, the particle size of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 is less than 50nm;

[0022] Preferably, the microstructure of the aluminum-based composite material further includes Al3Ti particles; wherein the particle size of the Al3Ti particles is less than 1 μm and is distributed in the aluminum matrix.

[0023] Preferably, the aluminum-based composite material is prepared by any of the above-mentioned methods for preparing an aluminum-based composite material that forms grain boundary and intragranular synergistic strengthening.

[0024] Compared with the prior art, the method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening of the present invention has at least the following beneficial effects:

[0025] On the one hand, an embodiment of the present invention provides a method for preparing an aluminum-based composite material with synergistic strengthening of grain boundaries and grains, which mainly includes the following steps: ball-milling and mixing raw material powders to obtain powder after ball-milling and mixing; wherein the raw material powders include aluminum powder, nano-TiO2 powder, and nano-Al2O3 powder; sintering the powder after ball-milling and mixing to obtain a sintered composite material; wherein, during the sintering process, Al and TiO2 react incompletely to generate an amorphous Al2O3 layer on the surface of the TiO2 particles to form a core-shell structure strengthening phase particle of amorphous Al2O3 coated TiO2; plastic processing is performed on the sintered composite material to promote the core-shell structure strengthening phase particle of amorphous Al2O3 coated TiO2 to enter the interior of the grains to obtain an aluminum-based composite material. It should be noted here about the above scheme that: for the Al-TiO2 system, the present invention adds nano-Al2O3 powder to the raw material powder, and on this basis, further suppresses the reaction between Al and TiO2 through process parameters, so that Al and TiO2 react incompletely during the sintering process, generates an amorphous Al2O3 layer on the surface of the TiO2 particles, forms a core-shell structure reinforcement phase particle of amorphous Al2O3 coated TiO2, and further promotes the amorphous Al2O3 through plastic processing. l2 The core-shell structure strengthening phase particles of O3 coated TiO2 enter the interior of the grains, and in the process of ball milling mixing and shaping processing (the entire preparation process), the nano-Al2O3 particles (that is, the nano-Al2O3 powder in the raw material, called the added nano-Al2O3 particles) are mainly distributed at the grain boundaries, thereby achieving synergistic reinforcement inside and outside the crystal, thereby improving the strength, plasticity and high temperature resistance of the aluminum-based composite material.

[0026] In summary, the method of the present invention is based on the in-situ reaction of Al-TiO2, and inhibits its full reaction by adding nano-Al2O3 particles to form core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2, and realizes its intracrystalline distribution, thereby obtaining an aluminum-based composite material with excellent strength and plasticity.

[0027] Compared with traditional high-temperature aluminum alloys and aluminum-based composite materials, the aluminum-based composite material prepared by the present invention has higher thermal stability and strong plasticity.

[0028] In the existing aluminum-based composite materials, Al-TiO2 completely reacts to generate (Al2O3+Al3Ti) / Al, where Al2O3 is difficult to escape from the grain boundary and enter the interior of the grain, resulting in a significant tendency for the grain boundary fracture of the material, and a large number of micron-sized Al3Ti particles are generated at the same time, which contribute very little to the high-temperature strength and are prone to fracture. Different from the corresponding technology, the core-shell structure strengthening phase particles formed by the incomplete reaction of the present invention are easy to enter the interior of the grain due to the presence of the surface amorphous layer, while the added nano Al2O3 particles are easy to stay at the grain boundary, thereby achieving grain boundary-intragranular synergistic strengthening. In addition, the present invention only generates a small amount of Al3Ti particles with extremely small size (less than 1μm), with higher strengthening efficiency, making the material mechanical properties more excellent.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of a method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0032] The inventive concept of the present invention is as follows: a method of doping an Al-TiO2 in-situ reaction system with externally added nano-Al2O3 particles to inhibit the full reaction of Al-TiO2 to form a core-shell structure strengthening phase of amorphous Al2O3 coated with TiO2. This strengthening phase is easy to enter the interior of the grain due to the presence of the surface amorphous layer, and the externally added nano-Al2O3 particles are easy to remain on the grain boundary, so that the grain boundary-intragranular synergistic strengthening can be achieved through further shaping processing to obtain a high-temperature resistant aluminum-based composite material with excellent strong plasticity. The scheme of the present invention is as follows:

[0033] On the one hand, an embodiment of the present invention provides a method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening, such as Figure 1 As shown, it mainly includes the following steps:

[0034] Ball milling and mixing treatment: ball milling and mixing treatment is performed on the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes aluminum powder, nano TiO2 powder, and nano Al2O3 powder.

[0035] Among the raw material powders, the average particle size of aluminum powder is 5 to 50 μm; the average particle size of nano-TiO2 powder is 15 to 40 nm; and the average particle size of nano-Al2O3 powder is 15 to 50 nm.

[0036] Among the raw material powders, the volume fraction of the nano-TiO2 powder is 3-8%, and the volume fraction of the nano-Al2O3 powder is 1-3%.

[0037] In the step of ball milling and mixing, the weight ratio of the ball to the material is 15:1 to 30:1, the maximum linear velocity of the grinding balls is greater than 3.5 m / s, and the time of the ball milling and mixing is 4 to 20 hours.

[0038] Powder metallurgy sintering treatment: the powder after ball milling mixing treatment is sintered to obtain a sintered composite material; wherein, during the sintering process: Al and TiO2 react incompletely, an amorphous Al2O3 layer is generated on the surface of the TiO2 particles, and a core-shell structure reinforcement phase particle of amorphous Al2O3 coated TiO2 is formed.

[0039] Before the sintering process, the powder after the ball milling and mixing process needs to be cold pressed to improve the density.

[0040] Wherein, the sintering treatment adopts any one of vacuum hot pressing sintering treatment, hot isostatic pressing sintering treatment, and discharge ion beam sintering treatment; the atmosphere is a vacuum atmosphere or a protective atmosphere. Wherein, the temperature of the sintering treatment is 580-645°C (preferably, the sintering treatment time is 1-5 hours). During the sintering process, Al and TiO2 react incompletely, and only an amorphous Al2O3 layer is generated on the surface layer of the TiO2 particles, forming a core-shell structure of amorphous Al2O3 coated TiO2. Due to the presence of the surface amorphous layer, such core-shell structure particles are more likely to enter the interior of the aluminum grains and pin dislocations.

[0041] Plastic processing: Plastic processing is performed on the composite material after sintering to promote the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 to enter the interior of the grains as the reinforcement phase to obtain an aluminum-based composite material.

[0042] Among them, in this step, the distribution of the strengthening phase can be regulated by plastic processing processes such as forging, rolling and extrusion, and the deformation temperature is 520-630°C (preferably, the deformation amount is 6-30:1), which can promote the core-shell structure strengthening phase particles of amorphous Al2O3 coated TiO2 to enter the interior of the grains. In addition, during the ball milling mixing treatment and shaping processing (the entire preparation process), the nano-Al2O3 particles are mainly distributed at the grain boundaries, thereby forming grain boundary-intragranular synergistic strengthening.

[0043] On the other hand, an embodiment of the present invention provides an aluminum-based composite material, wherein the microstructure of the aluminum-based composite material includes an Al matrix, amorphous Al2O3 coated TiO2 core-shell structure strengthening phase particles, and nano Al2O3 particles; wherein at least part of the amorphous Al2O3 coated TiO2 core-shell structure strengthening phase particles are located inside the grains; at least part of the Al2O3 particles are distributed at the grain boundaries; preferably, the amorphous Al2O3 coated TiO2 core-shell structure strengthening phase particles with a volume fraction of more than 50% are located inside the grains; preferably, the Al2O3 particles with a volume fraction of more than 80% are distributed at the grain boundaries; preferably, the particle size of the amorphous Al2O3 coated TiO2 core-shell structure strengthening phase particles is less than 50nm; preferably, the microstructure of the aluminum-based composite material also includes Al3Ti particles; wherein the particle size of the Al3Ti particles is less than 1μm and is distributed in the aluminum matrix. The Al2O3 particles with a volume fraction of more than 80% are distributed at the grain boundaries, and the remaining Al2O3 particles are located inside the grains.

[0044] The present invention is further described below by specific experimental examples:

[0045] Example 1

[0046] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0047] Ball milling and mixing treatment: ball milling the raw material powder to obtain the powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 5μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, the ball-to-material weight ratio is 20:1, the rotation speed is 350rpm, the maximum linear speed of the grinding ball is 4.4m / s, and the ball milling and mixing treatment time is 8 hours.

[0048] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0049] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0050] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 216MPa at 350°C and an elongation of 5%. The strength does not decrease after annealing at 350°C for 1000h. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0051] Example 2

[0052] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0053] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 40μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, with a ball-to-material weight ratio of 20:1, a rotation speed of 350rpm, a maximum linear speed of the grinding ball of 4.4m / s, and a ball milling and mixing treatment time of 8 hours.

[0054] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0055] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 10:1, to obtain an aluminum-based composite material.

[0056] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 210 MPa at 350°C and an elongation of 5%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0057] Example 3

[0058] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0059] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 20μm, nano TiO2 powder with an average particle size of 15nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, the ball-to-material weight ratio is 15:1, the rotation speed is 350rpm, the maximum linear speed of the grinding ball is 4.4m / s, and the ball milling and mixing treatment time is 8 hours.

[0060] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 1 hour.

[0061] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 20:1, to obtain an aluminum-based composite material.

[0062] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 220 MPa at 350°C and an elongation of 5%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0063] Example 4

[0064] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0065] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 20μm, nano-TiO2 powder with an average particle size of 40nm, and nano-Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano-TiO2 powder is 6%, and the volume fraction of nano-Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, with a ball-to-material weight ratio of 20:1, a rotation speed of 350rpm, a maximum linear speed of the grinding ball of 4.4m / s, and a ball milling and mixing treatment time of 8 hours.

[0066] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0067] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0068] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 206 MPa at 350°C and an elongation of 5.5%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0069] Example 5

[0070] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0071] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 20μm, nano TiO2 powder with an average particle size of 25nm, and nano Al2O3 powder with an average particle size of 15nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, with a ball-to-material weight ratio of 20:1, a rotation speed of 350rpm, a maximum linear speed of the grinding ball of 4.4m / s, and a ball milling and mixing treatment time of 8 hours.

[0072] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 645° C. and the vacuum sintering treatment time is 1 hour.

[0073] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 25:1, to obtain an aluminum-based composite material.

[0074] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 222MPa at 350°C and an elongation of 4.5%. The strength does not decrease after annealing at 350°C for 1000h. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0075] Example 6

[0076] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0077] Ball milling and mixing treatment: ball milling the raw material powder to obtain the powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 20μm, nano TiO2 powder with an average particle size of 25nm, and nano Al2O3 powder with an average particle size of 50nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, the ball-to-material weight ratio is 30:1, the rotation speed is 350rpm, the maximum linear speed of the grinding ball is 4.4m / s, and the ball milling and mixing treatment time is 8 hours.

[0078] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 4 hours.

[0079] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 630° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0080] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 203 MPa at 350°C and an elongation of 5%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0081] Example 7

[0082] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0083] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 16μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 8%, and the volume fraction of nano Al2O3 powder is 1%. The ball milling and mixing treatment is carried out in a high-energy ball mill, the ball-to-material weight ratio is 20:1, the rotation speed is 350rpm, the maximum linear speed of the grinding ball is 4.4m / s, and the ball milling and mixing treatment time is 20 hours.

[0084] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 580° C. and the vacuum sintering treatment time is 2 hours.

[0085] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0086] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 226MPa at 350°C and an elongation of 4%. The strength does not decrease after annealing at 350°C for 1000h. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0087] Example 8

[0088] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0089] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 16μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, the ball-to-material weight ratio is 20:1, the rotation speed is 350rpm, the maximum linear speed of the grinding ball is 4.4m / s, and the ball milling and mixing treatment time is 8 hours.

[0090] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 640° C. and the vacuum sintering treatment time is 2 hours.

[0091] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0092] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 206 MPa at 350°C and an elongation of 6%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0093] Example 9

[0094] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0095] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 15μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, with a ball-to-material weight ratio of 20:1, a rotation speed of 350rpm, a maximum linear speed of the grinding ball of 4.4m / s, and a ball milling and mixing treatment time of 8 hours.

[0096] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0097] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 520° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0098] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 215 MPa at 350°C and an elongation of 5%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0099] Example 10

[0100] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0101] Ball milling and mixing treatment: ball milling the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 15μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 6%, and the volume fraction of nano Al2O3 powder is 2%. The ball milling and mixing treatment is carried out in a high-energy ball mill, with a ball-to-material weight ratio of 20:1, a rotation speed of 350rpm, a maximum linear speed of the grinding ball of 4.4m / s, and a ball milling and mixing treatment time of 8 hours.

[0102] Powder metallurgy sintering treatment: vacuum sintering treatment is performed on the powder after ball milling mixing treatment to obtain a sintered composite material (sintered ingot); wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0103] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 630° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0104] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 210 MPa at 350°C and an elongation of 6%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0105] Comparative Example 1

[0106] Comparative Example 1: An aluminum-based composite material is prepared. Compared with Example 1, the average particle size of the TiO2 powder in the raw material powder in Comparative Example 1 is 150 nm.

[0107] Other steps and parameters are consistent with those in Example 1.

[0108] Here, since the average particle size of the TiO2 powder used in Comparative Example 1 is too large (it should be noted here that the ball milling treatment has little effect on the size of the strengthening phase due to being wrapped by aluminum powder), the core-shell structure strengthening phase particles of amorphous Al2O3 coated TiO2 are difficult to enter the interior of the grains, and high strength and toughness effects cannot be achieved.

[0109] Comparative Example 2

[0110] Comparative Example 2: An aluminum-based composite material is prepared. Compared with Example 1, the average particle size of the TiO2 powder in the raw material powder in Comparative Example 2 is 5 nm.

[0111] Other steps and parameters are consistent with those in Example 1.

[0112] Here, since the average particle size of the TiO2 powder in Comparative Example 2 is too small, during the sintering process, the TiO2 powder with a small particle size is very easy to react with aluminum, and it is impossible to generate amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles.

[0113] Comparative Example 3

[0114] Comparative Example 3: An aluminum-based composite material is prepared. Compared with Example 1, the average particle size of the nano-Al2O3 powder in the raw material powder in Comparative Example 3 is 150 nm.

[0115] Other steps and parameters are consistent with those in Example 1.

[0116] Here, since the average particle size of the nano-Al2O3 powder is too large and the surface area is small, the Al-TiO2 reaction cannot be suppressed and the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 cannot be formed.

[0117] Comparative Example 4

[0118] Comparative Example 4 prepares an aluminum-based composite material. Compared with Example 1, the average particle size of the nano-Al2O3 powder in the raw material powder in Comparative Example 4 is 5 nm.

[0119] Other steps and parameters are consistent with those in Example 1.

[0120] Here, since the average particle size of nano-Al2O3 powder is too small, it is very easy to enter the interior of the grains during ball milling and cannot inhibit grain boundary diffusion, so it is difficult to inhibit the Al-TiO2 reaction and cannot form amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles.

[0121] Comparative Example 5

[0122] Comparative Example 5: An aluminum-based composite material is prepared. Compared with Example 1, the temperature of the hot extrusion treatment in Comparative Example 4 is 400°C.

[0123] Other steps and parameters are consistent with those in Example 1.

[0124] Here, since the temperature of the hot extrusion treatment is too low, the aluminum matrix is ​​difficult to fully recrystallize during the extrusion process, and the strengthening phase cannot enter the interior of the grains, and the grain boundary-intragranular synergistic strengthening cannot be achieved.

[0125] Comparative Example 6

[0126] Comparative Example 6 prepares an aluminum-based composite material. Compared with Example 1, the sintering temperature in Comparative Example 6 is 550°C.

[0127] Other steps and parameters are consistent with those in Example 1.

[0128] Here, since the sintering temperature of Comparative Example 6 is too low, the in-situ reaction cannot be activated, and it is difficult to form amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles.

[0129] Comparative Example 7

[0130] Comparative Example 7 prepares an aluminum-based composite material. Compared with Example 1, the sintering temperature in Comparative Example 7 is 655°C.

[0131] Other steps and parameters are consistent with those in Example 1.

[0132] Here, since the sintering temperature of Comparative Example 7 is too high, Al-TiO2 is completely reacted, and it is difficult to form a core-shell structure reinforcement phase particle of amorphous Al2O3 coated TiO2.

[0133] Embodiment 11

[0134] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0135] Ball milling: ball milling the raw material powder to obtain a ball milled powder; wherein the raw material powder includes: aluminum powder with an average particle size of 16 μm, nano TiO2 powder with an average particle size of 20 nm, and nano Al2O3 powder with an average particle size of 20 nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 8%, and the volume fraction of nano Al2O3 powder is 3%. The ball milling is carried out in a high-energy ball mill with a ball-to-material ratio of 20:1, a rotation speed of 350 rpm, and a maximum linear speed of 4.4 m / s. The ball milling mixing treatment time is 8 hours.

[0136] Powder metallurgy sintering treatment: vacuum hot pressing sintering treatment is performed on the powder after ball milling treatment to obtain a sintered composite material; wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0137] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0138] The aluminum-based composite material obtained in this embodiment has excellent toughness and high temperature resistance. The tensile strength of the aluminum-based composite material at 350°C is 250MPa, the elongation is 3%, and the strength does not decrease after annealing at 350°C for 1000h. In the aluminum-based composite material: most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the added Al2O3 particles are located on the grain boundaries.

[0139] Example 12

[0140] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0141] Ball milling and mixing treatment: ball milling the raw material powder to obtain a powder after ball milling and mixing treatment; wherein the raw material powder includes: aluminum powder with an average particle size of 16μm, nano TiO2 powder with an average particle size of 20nm, and nano Al2O3 powder with an average particle size of 20nm. Among the raw material powders, the volume fraction of nano TiO2 powder is 3%, and the volume fraction of nano Al2O3 powder is 1%. The ball milling and mixing treatment is carried out in a high-energy ball mill, with a ball-to-material ratio of 20:1, a rotation speed of 350rpm, and a maximum linear speed of 4.4m / s. The ball milling and mixing treatment time is 8 hours.

[0142] Powder metallurgy sintering treatment: the powder after ball milling mixing treatment is subjected to vacuum hot pressing sintering treatment to obtain a sintered composite material (sintered ingot); wherein the temperature of the vacuum hot pressing sintering treatment is 620° C., and the time of the vacuum sintering treatment is 2 hours.

[0143] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0144] The aluminum-based composite material prepared in this embodiment has excellent toughness and high temperature resistance. Specifically, the aluminum-based composite material has a tensile strength of 180 MPa at 350°C and an elongation of 9%. The strength does not decrease after annealing at 350°C for 1000 hours. In the microstructure of the aluminum-based composite material prepared in this embodiment, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the nano-Al2O3 particles are located on the grain boundaries.

[0145] Embodiment 13

[0146] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0147] Ball milling: ball milling the raw material powder to obtain a ball milled powder; wherein the raw material powder includes: aluminum powder with an average particle size of 16 μm, nano TiO2 powder with an average particle size of 30 nm, and nano Al2O3 powder with an average particle size of 40 nm. wherein the volume fraction of the nano TiO2 powder in the raw material powder is 8%, and the volume fraction of the nano Al2O3 powder is 3%. wherein the ball milling is carried out in a high energy ball mill, with a ball to material ratio of 20:1, a rotation speed of 350 rpm, and a maximum linear speed of 4.4 m / s. the ball milling mixing treatment time is 8 hours.

[0148] Powder metallurgy sintering treatment: vacuum hot pressing sintering treatment is performed on the powder after ball milling treatment to obtain a sintered composite material; wherein the vacuum sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0149] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0150] The aluminum-based composite material obtained in this embodiment has excellent toughness and high temperature resistance. The tensile strength of the aluminum-based composite material at 350°C is 220MPa, the elongation is 5%, and the strength does not decrease after annealing at 350°C for 1000h. In the aluminum-based composite material: most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the added Al2O3 particles are located on the grain boundaries.

[0151] Embodiment 14

[0152] This embodiment prepares an aluminum-based composite material, which mainly includes the following steps:

[0153] Ball milling: ball milling the raw material powder to obtain the ball milled powder; wherein the raw material powder includes: aluminum powder with an average particle size of 16 μm, nano TiO2 powder with a particle size of 20 nm, and nano Al2O3 powder with a particle size of 40 nm. wherein the volume fraction of the nano TiO2 powder in the raw material powder is 8%, and the volume fraction of the nano Al2O3 powder is 3%. wherein the ball milling is carried out in a high energy ball mill, with a ball to material ratio of 20:1, a rotation speed of 350 rpm, and a maximum linear speed of 4.4 m / s. the ball milling mixing treatment time is 8 hours.

[0154] Powder metallurgy sintering treatment: vacuum hot pressing sintering treatment is performed on the ball-milled powder to obtain a sintered composite material; wherein the vacuum hot pressing sintering treatment temperature is 620° C. and the vacuum sintering treatment time is 2 hours.

[0155] Plastic processing: The sintered composite material is subjected to hot extrusion, wherein the temperature of the hot extrusion is 550° C. and the extrusion ratio is 16:1, to obtain an aluminum-based composite material.

[0156] The aluminum-based composite material obtained in this embodiment has excellent toughness and high temperature resistance. The tensile strength of the aluminum-based composite material at 350°C is 240MPa, the elongation is 3%, and the strength does not decrease after annealing at 350°C for 1000h. In the aluminum-based composite material, most of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 are located inside the grains, and most of the added Al2O3 particles are located on the grain boundaries.

[0157] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening, characterized in that: The preparation method of the aluminum-based composite material comprises the following steps: Ball milling and mixing treatment: ball milling and mixing treatment is performed on the raw material powder to obtain powder after ball milling and mixing treatment; wherein the raw material powder includes aluminum powder, nano-TiO2 powder, and nano-Al2O3 powder; Powder metallurgy sintering treatment: sintering the powder after the ball milling mixing treatment to obtain a sintered composite material; wherein, during the sintering process, Al and TiO2 react incompletely, and an amorphous Al2O3 layer is generated on the surface of the TiO2 particles, forming a core-shell structure reinforcement phase particle in which the amorphous Al2O3 covers the TiO2; Plastic processing: Plastic processing is performed on the composite material after the sintering process to promote the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 to enter the interior of the grains to obtain an aluminum-based composite material.

2. The method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening according to claim 1, characterized in that: In the raw material powder: The average particle size of the aluminum powder is 5 to 50 μm; and / or The average particle size of the nano-TiO2 powder is 15 to 40 nm; and / or The average particle size of the nano Al2O3 powder is 15 to 50 nm.

3. The method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening according to claim 1 or 2, characterized in that: In the raw material powder, the volume fraction of the nano-TiO2 powder is 3-8%, and the volume fraction of the nano-Al2O3 powder is 1-3%.

4. The method for preparing the aluminum-based composite material according to any one of claims 1 to 3, characterized in that: In the step of ball milling mixing: The ball-to-material weight ratio is 15:1 to 30:1; and / or The maximum linear speed of the grinding balls is greater than 3.5 m / s; and / or The ball milling mixing treatment time is 4 to 20 hours.

5. The method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening according to any one of claims 1 to 4, characterized in that: In the step of the powder metallurgy sintering process: Before sintering, the powder after the ball milling and mixing process needs to be cold pressed to improve the density.

6. The method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening according to any one of claims 1 to 5, characterized in that: In the step of powder metallurgy sintering treatment: the temperature of the sintering treatment is 580-645° C.; preferably, the sintering treatment time is 1-5 hours.

7. The method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening according to any one of claims 1 to 6, characterized in that: In the step of the powder metallurgy sintering process: The sintering process adopts any one of vacuum hot pressing sintering process, hot isostatic pressing sintering process and discharge ion beam sintering process.

8. The method for preparing an aluminum-based composite material with grain boundary and intragranular synergistic strengthening according to any one of claims 1 to 7, characterized in that: In the step of plastic processing: The temperature of the shaping process is 520-630°C; and / or The shaping process is any one of forging, rolling and extrusion; and / or The deformation amount of the shaping process is (6-30):

1.

9. An aluminum-based composite material, characterized in that: The microstructure of the aluminum-based composite material includes an Al matrix, amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles, and nano Al2O3 particles; wherein at least part of the amorphous Al2O3-coated TiO2 core-shell structure reinforcement phase particles are located inside the grains; at least part of the Al2O3 particles are distributed at the grain boundaries; Preferably, the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 with a volume fraction of more than 50% are located inside the grains; Preferably, Al2O3 particles with a volume fraction of more than 80% are distributed at the grain boundaries; Preferably, the particle size of the core-shell structure reinforcement phase particles of amorphous Al2O3 coated TiO2 is less than 50nm; Preferably, the microstructure of the aluminum-based composite material further includes Al3Ti particles; wherein the particle size of the Al3Ti particles is less than 1 μm and is distributed in the aluminum matrix.

10. The aluminum-based composite material according to claim 9, characterized in that: The aluminum-based composite material is prepared by the method for preparing an aluminum-based composite material for forming grain boundary and intragranular synergistic strengthening as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation and deformation method of Al2O3 / Al high-temperature-resistant aluminum-based composite material

    CN114574725A

  • Preparation method of aluminum-based composite material

    CN114635064A

  • Aluminum-based composite material and preparation method thereof

    CN116770120A

  • Amorphous aluminum oxide reinforced aluminum-based composite material and preparation method thereof

    CN117737497A

  • Aluminum-based composite material and preparation method thereof

    CN118880094A